The Case for Government Supported Training Program - Gunderson, Morely (Relations industrielles / Industrial Relations, 1974)
Concepts of Public Expenditure Economies are applied to the operation of labour markets in general and training programs in particular to see if the free market provides a socially optimal amount of training. The case for government-supported training is discussed when there exist market imperfections and equity considerations, as well as market failure due to externalitiesyhigh risk and uncertainty, and merit goods.